Reintroducing threatened pine-associated fungal species in boreal forests - Crosier, Joette; Penttilä, Reijo; Miettinen, Otto; Furneaux, Brendan; Pennanen, Jorma; Hamberg, Leena (Springer Nature, 2025)
Many species of wood-inhabiting fungi, particularly in the boreal forests of Nordic countries, face significant extinction risks. The historical impact of commercial forestry has led to fragmented old-growth forests, meaning that species lost from these areas may not naturally return to newly protected habitats. This study investigates the potential of inoculation as a management tool to aid the reintroduction of threatened fungal species. Specifically, we tested whether red-listed fungal species associated with dead pine wood could successfully establish in inoculated pine logs and identified factors influencing inoculation success. We cultured mycelium from five target species (Anthoporia albobrunnea, Antrodia crassa, Antrodia infirma, Crustoderma corneum, Dichomitus squalens) and inoculated pine logs in selected forests, monitoring log characteristics and conducting DNA analysis of the fungal community before and after inoculation. Our findings demonstrate that all species successfully established in at least some of the inoculated logs (28–60% success), with variable effects of log characteristics on fungal abundance. Additionally, the presence of certain fungi correlated with the success of the inoculated species. These results suggest that inoculation can be a promising method for aiding the recovery of threatened wood-inhabiting fungi in appropriate forest habitats. Long-term monitoring is necessary to assess fruiting success and population sustainability, while further exploration of alternative techniques could enhance the effectiveness of reintroduction efforts in forest management practices.
Keywords: inoculation; biodiversity; red-list; conservation